Inggris - Amna Mawardi Mawardi; Dedeng Abdul Gani Amruloh; Afifah Azhnie Nur Arvira (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
This research was conducted to determine the influence of green transformational leadership and knowledge environment on Pro-Environmental Behavior of students in economics in the society era in Purwakarta. In this study using variables green transformational leadership and knowledge environment as independent variables. Primary data were collected from a sample of 98 respondents. The data analysis method used in this study is multiple linear regression with the help of SPSS 25 software. Based on the results of research that has been conducted shows that partially green transformational leadership and environmental knowledge have a positive and significant effect on Pro-Environmental behavior. And all independent variables have a simultaneous effect on Pro-Environmental Behavior with a calculated F value of 67.150 with a significance level of 0.000. And the R square value shows a result of 0.681 which means that all independent variables have a simultaneous effect of 68.1%.